Integration of AI Chatbots in Islamic Religious Education: Potential and Challenges from a Doctoral Student Perspective - Mohammad Sholeh; Evi Fatimatur Rusydiyah; M. Yunus Abu Bakar (AL-ISHLAH: Jurnal Pendidikan, 2024)
This article examines the application of artificial intelligence (AI), particularly chatbot technology such as ChatGPT, in higher education, with a specific focus on Islamic religious learning.  The study involved 27 doctoral students from Sunan Ampel State Islamic University, Surabaya, using a survey method to explore their perceptions of ChatGPT in Islamic religious learning. Data was obtained via Google Forms using purposive and convenience sampling techniques. The survey contains 28 questions covering various aspects of ChatGPT's uses, benefits, limitations, and ethical issues. Data analysis using SPSS software, including frequency analysis, mean, and reliability. The results show a high level of reliability and reveal that using ChatGPT can improve productivity, learning quality, and personalization. However, there are limitations such as a lack of context understanding, limited personalization capabilities, and the potential to hinder human-to-human interactions. In addition, students also raised concerns about ethical issues such as plagiarism, assessment fairness, data privacy, dependency, and information bias. This article provides insights into the use of ChatGPT in higher education and emphasises the importance of considering ethical aspects in its implementation. To mitigate the ethical risks that may arise from the use of ChatGPT in educational settings, it is recommended that institutions develop policies, provide education, and ensure the availability of adequate resources. The article also emphasises the need for ethical risk mitigation measures associated with the use of ChatGPT in the educational environment.